Cyberbullying Victimization as a Predictor of Depressive Symptoms among Selected Adolescents amidst the COVID-19 Pandemic - Maria Michael, Jeyaseelan; Reyes, Marc Eric (Makara Human Behavior Studies in Asia, 2021)
Cyberbullying victimization has become a significant mental health concern, particularly among adolescents at risk of experiencing negative consequences like depression. As the outbreak of the Covid-19 pandemic forced everyone to stay at home and participate in all their educational, recreational, and entertainment activities online, this study investigated the relationship between cyberbullying victimization (CV) and depressive symptoms among 612 college students in Tamilnadu, India. We hypothesized that experiences of cyberbullying victimization would predict depressive symptoms among the participants. Adolescent participants aged 18 to 19 years old from colleges in Tamilnadu completed an online survey composed of the Cybervictimization questionnaire for adolescents (CYVIC) and the Beck Depression Inventory-II (BDI-II). Results obtained show a very strong positive relationship between cyberbullying victimization and depression, with CV being a very strong predictor in the relationship. Moreover, impersonation, written-verbal cyber victimization, visual-teasing/happy slapping, and online exclusion contributing highly to the strong positive relationship between the variables. These findings can be a foundation for intervention programs to alleviate depressive symptoms by addressing CV experiences and focus on further research on the negative consequences of cyberbullying victimization among adolescents.